Where do mountains and hills come from? - Malabed, Liwliwa N.; Espiritu, Iori Janelli; Agbayani-Pastor, Boots S. (Quezon City : Lampara Publishing House, 2013)
""Where do mountains and hills come from?" a curious little boy asks. Find out in this story the answers the little boy gets from various living creatures. The answers are varied and different from each other, but all focus on a singular crucial issue$1 (Bevery person's responsibility to the world in which he lives."--Covers
In English and Filipino.
Keywords: Mountains -- Juvenile fiction; Children's stories, Filipino